An Error Analysis of Writing Hamzat al-Waṣl and Hamzat al-Qaṭʿ in the Book Al-Naḥw al-Wāḍiḥ - Dewi Nurhayati; Dzuryati Afifah; Moh. Wardi (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2022)
The Book “al_Nahw al-Wadih”, Volume Two, printed at the expense of the Bali Library Buku Surabaya. It is one of the books that students use in the education process, especially in schools and institutes. However, researchers found several errors in writing the hamzat al-wasl and hamzat al-qat’ in this particular book in the chapter “Taqsim al-Fi’li ila Shahih al-Akhir wa Mu’tal al-Akhir” This research aims to know the misspelled words and to know the writing of the correct words from the misspelled words in the writing of Hamzat al-Wasl and Hamzat al-Qata’ in that particular book in the chapter “Taqsim al-Fi’li ila Shahih al-Akhir wa Mu’tal al-Akhir” by Ali Al-Jarim and Mustafa Amin. In this research, the researchers used the qualitative descriptive approach, and the approach to research is desk research. The adjective in this research is descriptive and analytical. Then the two data sources used are primary data sources and secondary data sources. The method of data collection is the documentation method. The researchers used the method of content analysis based on the Ellis theory. It is the collection of erroneous words, identification of erroneous words, clarifying the erroneous words and matching them with correct grammar, detailing the erroneous words, and evaluating the erroneous words. The results in this research are that errors were found in writing the hamzat al-wasl with one word, and in writing the hamzat al-qat'a with 15 syllables. The correct writing in the writing of the hamzat al-wasl is written without the hamza in its alif (A), and in writing the hamzat al-qat’ it is written with the hamza in its alif